Syndrome of Accumulation of Air and Fluid in the Pleural Space (Pleurisy, Hydrothorax, Pneumothorax), Shortness of Breath, Diagnostics, General Understanding of Etiology and Pathogenesis - oʻgʻli, Murodullayev Bekjon Nurali; qizi, Sagdullayeva Dilsoʻz Rahim; qizi, Abdullayeva Nasiba Boboraxim; Qarshiboyevich, Rabbimov Muhammad Ali; qizi, Davlatova Durdona O'tkir; угли, Жумагелдиев Умиджон Эрали (PT. Antis International Publisher, 2024)
This article delves into the information about Syndrome of accumulation of air and fluid in the pleural space (pleurisy, hydrothorax, pneumothorax), shortness of breath and its diagnostics, as well as General understanding of etiology and pathogenesis.